Pemberdayaan Kelompok Wanita Tani Melalui Program Pertanian Terpadu dalam Ketahanan Pangan Keluarga: Studi pada Kelompok Wanita Tani Melati Desa Sukagalih Kec. Sukaratu Kab. Tasikmalaya - Rifda Nur Azkiyah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Women Farmer Groups play an important role in strengthening household food security, yet limited food diversity remains a challenge in rural communities. This study analyzes the empowerment process of the Melati Women Farmer Group (KWT Melati) through an integrated farming program in improving household food security in Sarengkol Hamlet, Sukagalih Village, Sukaratu District, Tasikmalaya Regency. The research employed a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, observation, and documentation. The findings show that the empowerment process was participatory, gradual, and sustainable, implemented through five stages. The enabling stage expanded women’s access and participation through social support and extension facilitation. The empowering stage strengthened technical and organizational capacities as well as women’s roles in decision-making. The protecting stage was reflected in social solidarity and mutual cooperation as informal protection. The supporting stage appeared through continuous assistance and community support. The maintaining stage indicated organizational independence despite reduced external aid. The study concludes that empowerment through integrated farming strengthens household food security based on social capital and women’s autonomy.